Analisis Kesesuaian Proses Legal Drafting Dengan Standar Pembentukan Peraturan Perundang-Undangan di Tingkat Daerah - Zaki Yamani, Akhmad (Zona Law And Public Administration Indonesia, 2024)
Regional autonomy in Indonesia grants local governments broad authority to draft Regional Regulations (Perda) as legal instruments for development. However, the drafting process often fails to comply with regulatory standards, resulting in non-implementable or conflicting regulations. This study aims to analyze the conformity of Perda drafting with legal standards and identify barriers and solutions to improve the process. A qualitative descriptive approach was employed, utilizing interviews, observations, and document analysis involving relevant stakeholders at the regional level. Key challenges include insufficient skilled personnel, weak understanding of drafting techniques, poor coordination, and limited budgets. Employing comprehensive academic manuscripts and collaboration with academics significantly enhance the quality of legal drafting. Strategic measures, such as intensive training and technical guidance, are essential for ensuring legal compliance. Improving the legal drafting process at the regional level requires capacity-building for personnel, detailed academic manuscripts, and strengthened inter-agency coordination to produce effective and lawful Perda